Hubungan Partisipasi Anak dalam Agro Educational Tourism dengan Minat pada Bidang Pertanian (Studi Kasus: Agrowisata Chelsea, Desa Taro, Kecamatan Tegallalang, Kabupaten Gianyar, Provinsi Bali) - AGREVINA, DESAK GEDE MAYA; ANGGRENI, I GUSTI A.A LIES; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.4, Oktober 2019, 2019)
The Relation of the Child’s Participation in Agro Educational Tourism to Their Interest in Agriculture (A Case Study: Chelsea Agrotourism, TaroVillage, Tegallalang District, Gianyar Regency. Bali Province) It seems that the young generation’s interest in agriculture has decreased in the last several years. The decrease in the number of young people who work as farmers and the decrease in the number of agricultural graduates show this. The Agro Educational Tourism is a combination of the agro-touristic activities and the concept of education which is intended to promote agriculture widely. The Chelsea Agrotourism developed at Taro Village, Tegalallang District, Gianyar Regency, Bali Province shows the concept of the education-based tourism. In this case, children are the target of tourists. Therefore, it was necessary to conduct research on the relationship of the children’s participation in agro educational tourism to their interest in agriculture. The children’s participation can inspire the young generation to choose agricultural education. The result of the study showed that the children involving in the outing activity offered by the Chelse Agrotourism showed highly active participation. Their participation was positively relevant to their interest. When their participation improves, their interest will be better. It can be concluded, therefore, that it is good to promote the Agro Educational Tourism to improve the children’s interest in agriculture.